(untitled) (Contextos: Estudios de Humanidades y Ciencias Sociales, 2017)
The main objective of the present study is to compare the indicators of television viewer’s profile of 283 adolescents in order to identify cultural differences. The selected variables for the viewer’s profile are time in front of the t.v., parental mediation of media effects, reasons for choosing the favorite character, Identification and television gender preferences. The procedure is based on the application of CH- TV 0.2 questionnaire to adolescents between 15 and 19 years old of different parts of the country. The results show an average of 3 hours per week of time in front of the tv, increasing during the weekends. Tv series are the most favorite television gender, documentary programs are next, and sports are at the end of the list. The parental mediation type of restrictive (control) is the weakest, educational (instructive) and ludio (co-view) come next. There are differences among oities in relation to character preferences.